Influence of Knowledge, Motivation, and Family Support on Iron Supplement Adherence Among Pregnant Women for Anemia Prevention at a Public Health Center in Bojonegoro, Indonesia - Sri Wahyuni; Lilik Triyawati; Ari Tri Rahayu; Abdul Latip (Health Dynamics, 2026)
Background: Maternal Mortality Rate (MMR) is a crucial indicator for evaluating the success of a country's health development. In Indonesia, MMR remains high at 97.61 per 100,000 live births in 2020, falling short of the Sustainable Development Goals (SDGs) target of 70 per 100,000 live births by 2030. One contributing factor to this high rate is anemia during pregnancy. This study aims to analyze the influence of knowledge, motivation, and family support on pregnant women's adherence to consuming ferrous iron supplements as a preventive measure against pregnancy-related anemia in the working area of Kalitidu Public Health Center, Bojonegoro Regency. Methods: An analytical observational design with a cross-sectional approach was employed. The sample consisted of 167 pregnant women in their first, second, and third trimesters who agreed to participate. Data were collected through questionnaires and document reviews, and analyzed using multiple logistic regression tests. Results: Most respondents demonstrated adequate knowledge (89.3%), good motivation (87.3%), and strong family support (86.7%). Statistical analysis revealed a significant influence of knowledge, motivation, and family support on adherence to iron tablet consumption (p < 0.05). Conclusion: Educational interventions and social support play a vital role in improving compliance with iron supplementation, thereby reducing the prevalence of anemia and supporting the achievement of national MMR reduction targets.